Penerapan Legitime Portie Ahli Waris Terkait Penerima Manfaat pada Polis Asuransi Jiwa: Perspektif Perlindungan Hukum - Pangestika, Meitri Widya; Chandra, Tofik Yanuar (Universitas Islam Negeri Alauddin Makassar, 2024)
Life insurance has become an important necessity for today's modern society. In Indonesia, there is life insurance. As humans, we face risks in everyday life. Risk is an event that will occur but the timing is unknown or uncertain. Therefore, people enter into insurance agreements to be able to transfer the risk to the insurer, or insurance company Where the life insurance agreement provides security and health and guarantees the life and property of a person who is insured in accordance with the provisions stipulated in the insurance agreement. In addition, a life insurance agreement allows the insurer to be queath his wealth to his heirs. The method used in this research is normative juridical research, that is, research of library law or secondary data with sources of primary, secondary and tertiary legal materials. The research approach used is an analytical approach and a technique of collecting legal materials carried out by means of an inventory of positive legal rules, book literature, journals and other sources of legal materials. For the technique of analysis of legal materials is carried out by performing grammatical, systematic, and methodological interpretations of legal constructions. From the results of the study, it was obtained that life insurance, liability has the right to cash payments before the death of the world since the insurance agreement between the liability and the insurer is closed. If the responsibility of the world dies, the connoisseur has this data right as a right to come. Therefore, we will turn to the heirs. Payment of money for life insurance constitutes a guarantee, according to Article 1320 of the Civil Code and Article 257 of the Criminal Code related to the opinion of Diephuis and Opzoomer.